Tx/Rx Head Coil Induces Less RF Transmit-Related Heating than Body Coil in Conductive Metallic Objects Outside the Active Area of the Head Coil - Nagy, Zoltan; Oliver-Taylor, Aaron; Kuehne, Andre; Goluch, Sigrun; Weiskopf, Nikolaus (Frontiers in Neuroscience, 2017)
The transmit–receive (Tx/Rx) birdcage head coil is often used for excitation instead of the body coil because of the presumably lower risk of heating in and around conductive implants. However, this common practice has not been systematically tested. To investigate whether the Tx/Rx birdcage head coil produces less heating than the body coil when scanning individuals with implants, we used a 3T clinical scanner and made temperature measurements around a straight 15 cm conductor using either the Tx/Rx body or the head coil for excitation. Additionally, the transmitted fields of a Tx/Rx head coil were measured both in air and in gel using a resonant and a non-resonant B field probes as well as a non-resonant E field probe. Simulations using a finite-difference time domain solver were compared with the experimental findings. When the body coil was used for excitation, we observed heating around the 15 cm wire at various anatomical locations (both within and outside of the active volume of the head coil). Outside its active area, no such heating was observed while using the Tx/Rx head coil for excitation. The E and B fields of the Tx/Rx birdcage head coil extended well-beyond the physical dimensions of the coil. In air, the fields were monotonically decreasing, while in gel they were more complex with local maxima at the end of the ASTM phantom. These experimental findings were line with the simulations. While caution must always be exercised when scanning individuals with metallic implants, these findings support the use of the Tx/Rx birdcage head coil in place of the body coil at 3T in order to reduce the risk of heating in and around conductive implants that are remote from the head coil.